Recent Advances in Atmospheric Physics and Chemistry: Composition, Dynamics, and Impacts - Maneesha Singh (International Journal of Atmosphere, 2024)
The Earth's atmosphere is vital for sustaining life and regulating climate. This review explores key aspects of atmospheric physics and chemistry, including atmospheric composition, the dynamics of greenhouse gases, ozone depletion, and the effects of aerosols and atmospheric pollutants. The interaction between anthropogenic emissions and natural processes, such as the carbon and nitrogen cycles, is crucial for understanding climate feedback mechanisms. The impact of photochemistry on air quality and the implications of stratospheric and tropospheric chemistry are examined in detail. Advances in atmospheric modeling and remote sensing technologies have enhanced our understanding of atmospheric processes, leading to improved predictions of climate change and its associated effects. This review synthesizes recent research findings, highlighting the importance of monitoring atmospheric trace gases and their contribution to global warming and air pollution. By integrating various studies, we provide insights into emission sources, chemical kinetics, and the role of aerosols in climate systems. Understanding these interactions is critical for designing successful measures to combat climate change and enhance air quality.
Keywords: Air quality; Atmospheric composition; Photochemistry; aerosols; atmospheric dynamics; chemical kinetics; climate feedbacks; emission sources; greenhouse gases; ozone depletion